Association of cerebrospinal fluid volume with cerebral vasospasm after aneurysmal subarachnoid hemorrhage: a retrospective volumetric analysis - Scherer, Moritz; Jung, Jin-On; Wessels, Lars; Younsi, Alexander; Schönenberger, Silvia; Möhlenbruch, Markus Alfred; Maier-Hein, Klaus H.; Unterberg, Andreas; Zweckberger, Klaus (Neurocritical care, 2020)
In aneurysmal subarachnoid hemorrhage (SAH), clot volume has been shown to correlate with the development of radiographic vasospasm (VS), while the role of cerebrospinal fluid (CSF) volume remains largely elusive in the literature. We evaluated CSF volume as a potential surrogate for VS in addition to SAH volume in this retrospective series.